2019
DOI: 10.1111/tpj.14321
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of rhamnosyltransferase UGT89C1 from Arabidopsis thaliana reveal the molecular basis of sugar donor specificity for UDP‐β‐l‐rhamnose and rhamnosylation mechanism

Abstract: Glycosylation is a key modification for most molecules including plant natural products, for example, flavonoids and isoflavonoids, and can enhance the bioactivity and bioavailability of the natural products. The crystal structure of plant rhamnosyltransferase UGT89C1 from Arabidopsis thaliana was determined, and the structures of UGT89C1 in complexes with UDP-b-L-rhamnose and acceptor quercetin revealed the detailed interactions between the enzyme and its substrates. Structural and mutational analysis indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 46 publications
1
51
0
2
Order By: Relevance
“…F3GGT1 (flavonoid 3-O-glucoside GT 1) catalyze 1,2-xylosylation of anthocyanidin 3-O-glycosides (Montefiori et al, 2011;Yonekura-Sakakibara et al, 2012;Itkin et al, 2013). A few studies investigated the molecular basis of sugar-donor specificity of UGTs, but much more remains to be learned (Osmani et al, 2009;Chen and Li, 2017;Zong et al, 2019). For example, a single amino acid was identified to confer a change in sugar donor specificity in two UGT89A2 isoforms in Arabidopsis (Chen and Li, 2017).…”
Section: Ugts In Mba Biosynthesis Utilize Three Different Udp-sugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…F3GGT1 (flavonoid 3-O-glucoside GT 1) catalyze 1,2-xylosylation of anthocyanidin 3-O-glycosides (Montefiori et al, 2011;Yonekura-Sakakibara et al, 2012;Itkin et al, 2013). A few studies investigated the molecular basis of sugar-donor specificity of UGTs, but much more remains to be learned (Osmani et al, 2009;Chen and Li, 2017;Zong et al, 2019). For example, a single amino acid was identified to confer a change in sugar donor specificity in two UGT89A2 isoforms in Arabidopsis (Chen and Li, 2017).…”
Section: Ugts In Mba Biosynthesis Utilize Three Different Udp-sugarsmentioning
confidence: 99%
“…CcUGT4, which is specific for UDP-Xyl, contains a serine in this position. Using the first crystal structure of a rhamnosyltransferase, UGT89C1, Zong et al (2019) identified the histidine in position 357 in the PSPG-motif as a key amino acid for UDP-Rha specificity (Zong et al, 2019). Exchange with glutamine resulted in an enzyme that accepted both UDP-Rha and UDP-Glc.…”
Section: Ugts In Mba Biosynthesis Utilize Three Different Udp-sugarsmentioning
confidence: 99%
“…PSPG motif (total 44 amino acids in almost all identified family 1 GTs) is highly conserved in all glycosyltransferases involved in a plant specialized metabolism, as this motif is thought to correspond to a UDP-binding site (Caputi et al, 2012). Variations in PSPG motif had been demonstrated to play an important role in the UDP-sugar donor specificity of plant family 1 GTs (Noguchi et al, 2009; Ono et al, 2010; Zong et al, 2019). There are three amino acids difference in the PSPG motif of UGT76C4 and UGT76C5: position 6 (D in UGT76C5 vs .…”
Section: Resultsmentioning
confidence: 99%
“…A thorough look at plant UGTs capable of recognizing diverse donor sugars of UDP, GDP, and dTDP base such as UGT89C1 [ 58 ] could help into understanding the difference in the substrate flexibility. This UGT's crystal structure in complex with UDP-rhamnose and acceptor quercetin has been recently solved [ 16 ], which improves our understanding of the mechanism of glycosylation and UGT engineering to aid the production of bioactive glycosides. In plant UGTs, the C-terminal domains are highly similar leading to their recognition of same or similar donors.…”
Section: Discussionmentioning
confidence: 99%